2013
DOI: 10.1007/s00404-013-2866-0
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Does immediate postpartum curettage of the endometrium accelerate recovery from preeclampsia–eclampsia? A randomized controlled trial

Abstract: Immediate postpartum curettage is a safe and effective procedure and can accelerate recovery from pre-eclampsia or eclampsia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…However, both studies did suggest a reduction in the absolute number of eclamptic seizures in the curettage group compared with no intervention. 15 58 In one, however, there was a relevant difference between the study groups; 28/28 (100%) in the control group were eclamptic at enrolment, compared with 9/20 (45%) in the intervention group. 58 Four studies reported safety data, with none reporting any complications related to the intervention ( table 2B ).…”
Section: Resultsmentioning
confidence: 93%
See 3 more Smart Citations
“…However, both studies did suggest a reduction in the absolute number of eclamptic seizures in the curettage group compared with no intervention. 15 58 In one, however, there was a relevant difference between the study groups; 28/28 (100%) in the control group were eclamptic at enrolment, compared with 9/20 (45%) in the intervention group. 58 Four studies reported safety data, with none reporting any complications related to the intervention ( table 2B ).…”
Section: Resultsmentioning
confidence: 93%
“…Of the 39 studies, 9 (23%) included ≥100 participants, and only 2 studies included ≥200 participants. 15 16 Four were from lower middle-income settings 15 17–19 (classified according to the United Nations 20 ), and 13/39 (33%) studies had follow-up periods longer than 7 days (online supplementary appendix S4 ). Only 5/39 (13%) and 7/39 (18%) studies, respectively, reported maternal mortality or major maternal morbidity, and while the majority of studies did report some measure of BP control, three did not ( table 2A,B ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Two independent reviewers evaluated 162 potentially relevant studies. Seventy‐nine randomised trials reporting data from 31 615 maternal and 28 172 of their offspring met our inclusion criteria (Figure ) . Included trials evaluated 55 different interventions, of which 29 (37%) evaluated antihypertensive medication and 21 (27%) anticonvulsant medication (Table S1).…”
Section: Resultsmentioning
confidence: 99%